Development economics South Asia component - Ahmed Sadiq ed.; Annual Bank Conference on Development Economics; Annual bank conference on development economics Bangalore, India 2003 (New Delhi National Council of Applied Economic Research, 2004)
Theme covered in the volume relates to the Issues in Public Service Delivery, Globalisation and South Asia, Private Sector and Development, and Reforming Infrastructure.
Keywords: Development economics